DAMPAK EFEKTIVITAS DAN PENERAPAN SISTEM INFORMASI MANAJEMEN (SIM) TERHADAP PELAYANAN MASYARAKAT - Nurinaya, Nurinaya; Adil, Andi Nuzul (Universitas Muhammadiyah Parepare, 2019)
This study aims to find impact the Effectiveness and Application of Management Information Systems on Community Services at the Makassar City Trade Office. The type of research used in this study is quantitative causal research. The processed data is the result of distributing questionnaires to all employees of the Makassar City Trade Office with a sample of 91 respondents. The sampling method in this study uses purposive sampling. The data analysis technique used in this study is multiple linear regression. Based on the results of data analysis for the significance test t test showed that the Effectiveness variable (X1), the application of SIM (X2) partially had a positive and significant effect on Community Service at the Makassar City Trade Office. The implementation of Management Information System is the dominant variable influencing the Community Service.This study aims to find impact the Effectiveness and Application of Management Information Systems on Community Services at the Makassar City Trade Office. The type of research used in this study is quantitative causal research. The processed data is the result of distributing questionnaires to all employees of the Makassar City Trade Office with a sample of 91 respondents. The sampling method in this study uses purposive sampling. The data analysis technique used in this study is multiple linear regression. Based on the results of data analysis for the significance test t test showed that the Effectiveness variable (X1), the application of SIM (X2) partially had a positive and significant effect on Community Service at the Makassar City Trade Office. The implementation of Management Information System is the dominant variable influencing the Community Service.